Corona Concerts: The Effect of Virtual Concert Characteristics on Social Connection and Kama Muta - Swarbrick, Dana; Seibt, Beate; Grinspun, Noemi; Vuoskoski, Jonna K. (Frontiers in Psychology, 2021)
The popularity of virtual concerts increased as a result of the social distancing requirements of the coronavirus pandemic. We aimed to examine how the characteristics of virtual concerts and the characteristics of the participants influenced their experiences of social connection and kama muta (often labelled “being moved”). We hypothesized that concert liveness and the salience of the coronavirus would influence social connection and kama muta. We collected survey responses on a variety of concert and personal characteristics from 307 participants from 14 countries across 4 continents. We operationalized social connection as a combination of feelings and behaviours and kama muta was measured using the short kama muta scale (Zickfeld et al., 2019). We found that 1) social connection and kama muta were related and predicted by empathic concern, 2) live concerts produced more social connection, but not kama muta, than pre-recorded concerts, and 3) the salience of the coronavirus during concerts predicted kama muta and this effect was completely mediated by social connection. Exploratory analyses also examined the influence of social and physical presence, motivations for concert attendance, and predictors of donations. This research contributes to the understanding of how people can connect socially and emotionally in virtual environments.